Dry powder drag reducer for fracturing fluid and preparation method of dry powder drag reducer
The dry powder drag reducer preparation method using the synergistic effect of double-tailed hydrophobic monomers and modified SiO2/Fe3O4 nanoparticles solves the problems of slow dissolution rate of liquid drag reducers and poor performance in high-temperature environments, achieves efficient drag reduction performance and structural stability, and is suitable for fracturing fluid systems.
Patent Information
- Application Number
- CN202511220759.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-08-29
AI Technical Summary
Existing liquid drag reducers have a slow dissolution rate, are cumbersome to prepare, and are inconvenient to transport and store. Traditional dry powder drag reducers perform poorly in high-temperature environments and are prone to damaging pipelines and formations.
A dry powder drag reducer preparation method using a double-tailed hydrophobic monomer and modified SiO2/Fe3O4 nanoparticles in synergy is adopted. A stable three-dimensional network structure is formed through quaternization reaction and free radical polymerization, thereby enhancing heat resistance and shear resistance.
It improves the dissolution rate of the drag reducer and its drag reduction performance in high-salt environments, reduces fluid resistance, enhances the stability of the polymer structure and its resistance to thermal decomposition, and is suitable for high-temperature fracturing operations.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_8
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fracturing materials for drilling, and in particular to a dry powder drag reducer for fracturing fluid and a preparation method thereof. Background Art
[0002] During the drilling process for oil and gas field development, fracturing is generally required to achieve optimal production. Fracturing fluid is the working fluid in the fracturing process. It is pressurized by high-pressure pumping equipment and pumped into the formation at high speed through a tubing string. Currently, slickwater fracturing fluid is the most popular fracturing fluid. Its low viscosity and excellent fluidity effectively reduce pumping pressure and energy consumption during the fracturing process. Therefore, slickwater fracturing fluid systems have become a common fracturing technology in oil and gas field drilling.
[0003] To help cracks expand and increase gas well production, fracturing and production stimulation operations in oil and gas fields require the use of drag reducers. However, in large-scale, high-volume fracturing operations, traditional liquid drag reducers suffer from slow dissolution rates, cumbersome preparation, and inconvenient transportation and storage, making them difficult to meet the efficient and rapid demands of on-site construction. Therefore, the development of dry powder drag reducers with fast dissolution rates, low damage, and excellent drag reduction performance has become a top priority.
[0004] Existing dry powder drag reducers include natural polymers and synthetic polymers. Natural polymers are biodegradable drag reducers, primarily including xanthan gum, guar gum, and their derivatives. They are reasonably priced and readily available, making them a common drag reducer for fracturing fluids. However, using natural polymers alone as drag reducers has some drawbacks. They take too long to hydrate and swell during fluid preparation, are prone to biodegradation underground, and cannot be used in high-temperature environments, thus affecting drag reduction performance.
[0005] Most synthetic polymers are polyacrylamide polymers, which primarily exist in powder form. With mature manufacturing processes and ease of transportation, polyacrylamide polymers are a common drag reducer for slick water in oil fields. This type of polymer is primarily composed of acrylamide and other functional monomers, which undergo free radical polymerization using a suitable initiation system to form a gel. The gel is then dried and crushed into polymer powders of varying mesh sizes. Polyacrylamide can be classified into anionic, cationic, nonionic, and amphoteric types based on its ionization in aqueous solution. Different monomer types influence the various properties of the drag reducer. For example, the hydrophilic sulfonate group can form a stable hydrogen bond structure with water molecules, which can then be copolymerized with acrylamide monomers to enhance the polymer's resistance to temperature and salt. However, this type of powdered polymer has poor distribution and solubility in water, leading to uneven mixing of the fracturing fluid, which can damage the pipeline and formation, hindering secondary recovery.
[0006] Therefore, it is necessary to provide a dry powder drag reducer for fracturing fluid and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Summary of the Invention
[0007] In view of this, the present invention provides a dry powder drag reducer for fracturing fluid and a preparation method thereof, which can achieve good drag reduction performance while having certain heat resistance, and can be better applied to fracturing operations in the drilling process.
[0008] To achieve the above object, the present invention provides a method for preparing a dry powder drag reducer for fracturing fluid, comprising the following steps: S1. Dissolve 4-bromobutyryl chloride and N-dodecylmethylamine in acetonitrile, heat and stir to react, add polyethylene glycol monomethyl ether acrylate and dichloromethane, stir and react under nitrogen atmosphere, wash, separate, and rotary evaporate to obtain a double-tailed hydrophobic monomer; S2, adding the core-shell SiO2 / Fe3O4 composite nanoparticles to an ethanol aqueous solution, ultrasonically dispersing them, then adding KH570 and ammonia solution, stirring continuously for reaction, and then distilling under reduced pressure, centrifuging, collecting the precipitate, washing, and vacuum drying to obtain modified SiO2 / Fe3O4; S3. Add acrylamide, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid sodium salt, a double-tailed hydrophobic monomer, and modified SiO2 / Fe3O4 into deionized water and mix well. After adjusting the pH value, introduce nitrogen gas into the mixture and stir. Add an azo initiator, continue stirring to react, cool to room temperature, wash, filter, vacuum dry, and grind into powder to obtain a dry powder drag reducer.
[0009] The present invention obtains a double-tailed hydrophobic monomer through a two-step synthesis reaction, further enhancing salt tolerance and shear resistance, and increasing the polymer's associative strength with minimal dosage. The specific reaction formula is as follows:
[0010] First, a quaternization reaction is carried out using 4-bromobutyryl chloride and N-dodecylmethylamine to obtain a quaternary ammonium salt. The quaternary ammonium salt is then acylated with polyethylene glycol monomethyl ether acrylate to obtain a double-tailed hydrophobic monomer, which includes a combination of a long-chain hydrophilic polyethylene glycol segment (PEO) and two hydrophobic C12 chains on the quaternary ammonium salt ion. The longer PEO segment is highly hydrophilic and flexible. The long PEO chain increases the distance between the hydrophobic groups, acting as a spatial barrier, effectively reducing the possibility of strong intramolecular association between the hydrophobic groups or early agglomeration of the molecular chains, ensuring that the molecular chains can be relatively stretched and dispersed in water in the initial stage of dissolution. In addition, the PEO segment can quickly hydrate with water molecules, greatly promoting the hydrophilicity and dissolution kinetics of the polymer chain, which can increase the dissolution rate of the final polymer in water, thereby improving the overall drag reduction performance and better application in fracturing operations during drilling.
[0011] The present invention introduces a double-tailed hydrophobic monomer and modified SiO2 / Fe3O4 into a free radical polymerization reaction to obtain a final polymer, the specific structural formula of which is as follows:
[0012] The longer hydrophilic ethylene oxide chain of the double-tailed hydrophobic monomer can extend the double-tailed hydrophobic chain to a farther position, and also greatly increase the space volume occupied by each repeating unit, effectively inhibiting the formation and development of pulsating vortexes, increasing the thickness of the buffer zone and thus playing a role in reducing fluid resistance; with the addition of more double-tailed hydrophobic side chains in the double-tailed hydrophobic monomer, the interaction between the molecular chains is increased, forming a strong and stable three-dimensional network structure. In addition, based on the unique rigid structure of the modified SiO2 / Fe3O4, it is introduced as a monomer into the polymer structure, and the multiple cross-linking effect achieved by physical adsorption and chemical bonding is utilized to enhance the strength of the polymer network structure. The double-tailed hydrophobic monomer and the modified SiO2 / Fe3O4 work together to improve the The shear resistance of the high drag reducer; and the interaction between the polymer structure and the modified SiO2 / Fe3O4 can effectively delay structural degradation, improve the polymer structure's resistance to thermal decomposition, and further improve heat resistance; the sulfonic acid group in 2-acrylamido-2-methylpropanesulfonic acid sodium salt has extremely strong ionization ability, and can maintain a negative charge even at high salt concentrations, providing a long-lasting electrostatic repulsion, inhibiting excessive curling of the molecular chain, and synergistically modifying SiO2 / Fe3O4 to provide a rigid skeleton support, which can prevent the network from completely collapsing even when the charge is shielded and the chain curls up to a certain extent, maintaining its basic structure and viscoelasticity. The two synergistically give the overall good salt resistance, enabling it to achieve better fracturing effects in high-salt water layers or oil and gas layers. Optionally, in step S1, 4-bromobutyryl chloride and N-dodecylmethylamine are dissolved in acetonitrile, and the mixture is mixed and stirred at a reaction temperature of 70-80°C and a speed of 500 rpm for 20-40 minutes, and then polyethylene glycol monomethyl ether acrylate is added, and dichloromethane is added dropwise. After continuous stirring for 45-48 hours under a nitrogen atmosphere at 0°C, the mixture is washed 2-5 times with dichloromethane and a sodium bicarbonate solution with a mass concentration of 8.2%, respectively, and then separated in a separation funnel and rotary evaporated to obtain a double-tailed hydrophobic monomer.
[0013] Optionally, the core-shell SiO2 / Fe3O4 composite nanoparticles are obtained by mixing an ethanol aqueous solution, Fe3O4 colloid and ethyl orthosilicate under continuous stirring, adding ammonia water, stirring at 300 rpm for 5 to 7 hours, centrifuging at 10,000 rpm for 10 to 15 minutes, taking the precipitate, and washing it with deionized water and anhydrous ethanol for 3 to 5 times respectively.
[0014] Optionally, the volume concentration of the ethanol aqueous solution is 80%, and the volume concentration of the ammonia water is 25%.
[0015] Optionally, the stirring reaction is carried out under sealed conditions, and after washing with deionized water and anhydrous ethanol for 3 to 5 times respectively, magnetic separation is performed to finally obtain core-shell SiO2 / Fe3O4 composite nanoparticles.
[0016] The modified SiO2 / Fe3O4 has magnetic responsiveness, and the drag reducer can be efficiently recovered through an external magnetic field after use, avoiding residual pollution of the system or the environment, reducing the cost of use, and possibly achieving recycling. In addition, in local high turbulence areas, the polymer can be directionally manipulated through an external magnetic field to enrich it in key areas (such as near the pipe wall), thereby precisely enhancing the drag reduction effect.
[0017] Optionally, the Fe3O4 colloid is prepared by mixing FeCl3·6H2O and Na2SO3 solutions under nitrogen protection and stirring for 10 minutes, rapidly adding ammonia water to mix, heating to 70°C and adding sodium citrate solution, stirring continuously at 500 rpm for 1-2 hours, centrifuging at 8000 rpm for 10-15 minutes, collecting the precipitate, washing with deionized water for 3-5 times, and finally dispersing in deionized water to obtain the colloid.
[0018] Here, ammonia provides an alkaline environment, promoting the hydrolysis of metal ions and the formation of iron oxides. Sodium citrate ensures the dispersion and stability of the product through complexation.
[0019] Optionally, the molar concentration of the Na2SO3 solution is 0.5 mol / L, the mass concentration of the sodium citrate solution is 1%, and the volume concentration of the ammonia water is 25%.
[0020] Optionally, in step S3, acrylamide, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid sodium salt, a double-tailed hydrophobic monomer, and modified SiO2 / Fe3O4 are added to deionized water and mixed evenly, sodium hydroxide is added to adjust the pH value to 6.0-6.5, nitrogen is introduced into the solution and the mixture is stirred for 30-40 minutes, an azo initiator is added, and the mixture is stirred continuously at 40-50°C at a speed of 450 rpm for 5-8 hours, then cooled to room temperature, washed with anhydrous ethanol 3-5 times, the product is collected by filtration, vacuum dried at 40-50°C for 16-24 hours, and crushed into powder to obtain a dry powder drag reducer.
[0021] Azo initiators trigger free radical polymerization during the polymerization reaction, decomposing at temperatures between 40°C and 50°C to produce free radicals, which initiate the polymerization of monomers such as acrylamide and acrylic acid. The generation of free radicals accelerates the polymerization reaction; the product is crushed into a fine powder for easy subsequent use.
[0022] Optionally, the azo initiator is azobisisobutylamidine hydrochloride.
[0023] The present invention also provides a dry powder drag reducer for fracturing fluid, comprising the following raw materials in parts by mass: 90-100 parts of acrylamide, 8-10 parts of acrylic acid, 2-3.5 parts of 2-acrylamido-2-methylpropanesulfonic acid sodium salt, 0.2-0.3 parts of a double-tailed hydrophobic monomer, 1.2-1.5g parts of modified SiO2 / Fe3O4, and 0.39-0.43 parts of an azo initiator.
[0024] The above technical solution of the present invention includes at least the following beneficial effects: 1. The double-tailed hydrophobic monomer ensures the hydrophilicity and dispersibility of the polymer through the flexibility and spatial barrier effect of the PEO chain segment. The PEO chain segment greatly promotes the hydrophilicity and dissolution dynamics of the polymer chain, which can increase the dissolution rate of the final polymer in water.
[0025] 2. This invention utilizes the synergistic effect of a double-tailed hydrophobic monomer and modified SiO2 / Fe3O4 to form a stable polymer during free radical polymerization. The hydrophilic PEO segments extend the hydrophobic chains, suppressing pulsating vortices, reducing fluid resistance, and increasing the thickness of the buffer zone. The modified SiO2 / Fe3O4 enhances the polymer's three-dimensional network structure, improving shear and heat resistance. The ionization and salt tolerance of the sulfonic acid groups further enhance the polymer's stability, ensuring it maintains structural strength and viscoelasticity in high-salt environments, resulting in excellent drag-reducing properties. DETAILED DESCRIPTION
[0026] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention. All other embodiments obtained by ordinary technicians in this field based on the described embodiments of the present invention are within the scope of protection of the present invention.
[0027] Example 1
[0028] After dissolving 1.2 g of 4-bromobutyryl chloride and 1.6 g of N-dodecylmethylamine in 35 mL of acetonitrile, the mixed solution was poured into a three-necked round-bottom flask equipped with a thermometer, reflux condenser, and dropping funnel. After mixing and stirring at a reaction temperature of 70°C and a speed of 500 rpm for 20 min, 3.9 g of polyethylene glycol monomethyl ether acrylate was added, and 35 mL of dichloromethane was added dropwise using a dropping funnel. After continuous stirring for 45 h under a nitrogen atmosphere at 0°C, the crude product was washed twice with dichloromethane and 8.2% sodium bicarbonate solution, respectively, and then separated in a separatory funnel. The dichloromethane and acetonitrile were removed by rotary evaporation to obtain a double-tailed hydrophobic monomer (brown-yellow thick oily liquid).
[0029] 5.4 g of FeCl3·6H2O was placed in a 500 mL three-necked flask. Under nitrogen protection, 40 mL of 0.5 mol / L Na2SO3 solution was added and stirred for 10 min. Then, 6.7 mL of 25% ammonia water was quickly added and mixed. Black particles were formed. The temperature was raised to 70 ° C in a constant temperature water bath and 50 mL of 1% sodium citrate solution was added. The mixture was stirred at 500 rpm for 1 h. The mixture was centrifuged at 8000 rpm for 10 min. The precipitate was washed with deionized water for 3 times and finally dispersed in 50 mL of deionized water to obtain a stable Fe3O4 colloid. Under continuous stirring, 100 mL of 80% ethanol aqueous solution, 50 mL of Fe3O4 colloid and 0.42g of ethyl orthosilicate were added, and then 2.7mL of 25% ammonia water was added. The mixture was sealed and stirred at 300rpm for 5h, and then centrifuged at 10000rpm for 10min. The precipitate was taken and washed with deionized water and anhydrous ethanol three times respectively, and finally magnetic separation was used to obtain core-shell SiO2 / Fe3O4 composite nanoparticles.
[0030] 5 g of core-shell SiO2 / Fe3O4 composite nanoparticles were added to 40 mL of 80% ethanol aqueous solution and ultrasonically dispersed at a power of 300 W for 30 minutes. Subsequently, 0.2 g of KH570 (CAS number: 2530-85-0) and 1 mL of 25% ammonia solution were added. After continuous stirring at 300 rpm in a nitrogen environment at 50°C for 8 hours, the excess ethanol was removed by vacuum distillation, and the mixture was centrifuged at 10,000 rpm for 10 minutes. The precipitate was taken, washed three times with anhydrous ethanol, and vacuum dried at 60°C for 18 hours to obtain modified SiO2 / Fe3O4.
[0031] 100 g of acrylamide, 10 g of acrylic acid, 3.5 g of 2-acrylamido-2-methylpropanesulfonic acid sodium salt, 0.3 g of a double-tailed hydrophobic monomer, and 1.5 g of modified SiO2 / Fe3O4 were added to 600 mL of deionized water and mixed evenly. Sodium hydroxide was added to adjust the pH value to 6.0. Nitrogen was introduced into the solution and stirred for 30 minutes. Then, 0.43 g of azobisisobutylamidine hydrochloride (CAS No.: 2997-92-4) was added. The mixture was stirred at 50°C and 450 rpm for 5 hours, then cooled to room temperature, washed three times with anhydrous ethanol, and the product was collected by filtration. It was vacuum dried at 50°C for 24 hours and pulverized into powder to prepare a dry powder drag reducer.
[0032] Example 2
[0033] After dissolving 1.2 g of 4-bromobutyryl chloride and 1.6 g of N-dodecylmethylamine in 35 mL of acetonitrile, the mixed solution was poured into a three-necked round-bottom flask equipped with a thermometer, reflux condenser, and dropping funnel. After mixing and stirring at a reaction temperature of 80°C and a speed of 500 rpm for 40 minutes, 3.9 g of polyethylene glycol monomethyl ether acrylate was added, and 35 mL of dichloromethane was added dropwise using a dropping funnel. After continuous stirring under a nitrogen atmosphere at 0°C for 48 hours, the crude product was washed five times with dichloromethane and 8.2% sodium bicarbonate solution, respectively. The product was then separated in a separatory funnel and the dichloromethane and acetonitrile were removed by rotary evaporation to obtain a double-tailed hydrophobic monomer (a brownish-yellow thick oily liquid).
[0034] 5.4 g of FeCl3·6H2O was placed in a 500 mL three-necked flask. Under nitrogen protection, 40 mL of 0.5 mol / L Na2SO3 solution was added and stirred for 10 min. Then, 6.7 mL of 25% ammonia water was quickly added and mixed. Black particles were formed. The temperature was raised to 70 ° C in a constant temperature water bath and 50 mL of 1% sodium citrate solution was added. The mixture was stirred at 500 rpm for 2 h. The mixture was centrifuged at 8000 rpm for 15 min. The precipitate was washed with deionized water for 5 times and finally dispersed in 50 mL of deionized water to obtain a stable Fe3O4 colloid. Under continuous stirring, 100 mL of 80% ethanol aqueous solution, 50 mL of Fe3O4 colloid and 0.42g of ethyl orthosilicate were added, and then 3mL of 25% ammonia water was added. The mixture was sealed and stirred at 300rpm for 7h, and then centrifuged at 10000rpm for 15min. The precipitate was taken and washed with deionized water and anhydrous ethanol for 5 times respectively, and finally magnetic separation was used to obtain core-shell SiO2 / Fe3O4 composite nanoparticles.
[0035] 5 g of core-shell SiO2 / Fe3O4 composite nanoparticles were added to 40 mL of 80% ethanol aqueous solution and ultrasonically dispersed at a power of 300 W for 30 minutes. Subsequently, 0.25 g of KH570 (CAS number: 2530-85-0) and 1 mL of 25% ammonia solution were added. After continuous stirring at 300 rpm in a nitrogen environment at 65°C for 12 hours, the excess ethanol was removed by vacuum distillation, and the mixture was centrifuged at 10,000 rpm for 10 minutes. The precipitate was collected, washed with anhydrous ethanol 5 times, and vacuum dried at 60°C for 24 hours to obtain modified SiO2 / Fe3O4.
[0036] 90 g of acrylamide, 8 g of acrylic acid, 2 g of 2-acrylamido-2-methylpropanesulfonic acid sodium salt, 0.2 g of a double-tailed hydrophobic monomer, and 1.2 g of modified SiO2 / Fe3O4 were added to 550 mL of deionized water and mixed evenly. Sodium hydroxide was added to adjust the pH value to 6.5. Nitrogen was introduced into the solution and mixed and stirred for 40 minutes. Then, 0.39 g of azobisisobutylamidine hydrochloride (CAS No.: 2997-92-4) was added. The mixture was stirred at 450 rpm at 40°C for 8 hours, then cooled to room temperature, washed with anhydrous ethanol 5 times, and the product was collected by filtration. It was vacuum dried at 40°C for 24 hours and pulverized into powder to obtain a dry powder drag reducer.
[0037] Example 3
[0038] 1.2 g of 4-bromobutyryl chloride and 1.6 g of N-dodecylmethylamine were dissolved in 35 mL of acetonitrile, and the mixed solution was poured into a three-necked round-bottom flask equipped with a thermometer, reflux condenser, and dropping funnel. After mixing and stirring at 500 rpm for 30 min at a reaction temperature of 75°C, 3.9 g of polyethylene glycol monomethyl ether acrylate was added, and 35 mL of dichloromethane was added dropwise using a dropping funnel. After continuous stirring for 47 h under a nitrogen atmosphere at 0°C, the crude product was washed three times with dichloromethane and 8.2% sodium bicarbonate solution, respectively, and then separated in a separatory funnel. The dichloromethane and acetonitrile were removed by rotary evaporation to obtain a double-tailed hydrophobic monomer (a brown-yellow thick oily liquid).
[0039] 5.4 g of FeCl3·6H2O was placed in a 500 mL three-necked flask. Under nitrogen protection, 40 mL of 0.5 mol / L Na2SO3 solution was added and stirred for 10 min. Then, 6.7 mL of 25% ammonia water was quickly added and mixed. Black particles were formed. The temperature was raised to 70 ° C in a constant temperature water bath and 50 mL of 1% sodium citrate solution was added. The mixture was stirred at 500 rpm for 1.5 h, and then centrifuged at 8000 rpm for 12 min. The precipitate was washed with deionized water 4 times and finally dispersed in 50 mL of deionized water to obtain a stable Fe3O4 colloid. Under continuous stirring, 100 mL of 80% ethanol aqueous solution, 50 mL of Fe3O4 colloid and 0.42g of ethyl orthosilicate were added, and then 2.8mL of 25% ammonia water was added. The mixture was sealed and stirred at 300rpm for 6h, and then centrifuged at 10000rpm for 12min. The precipitate was taken and washed with deionized water and anhydrous ethanol four times respectively, and finally magnetic separation was used to obtain core-shell SiO2 / Fe3O4 composite nanoparticles.
[0040] 5 g of core-shell SiO2 / Fe3O4 composite nanoparticles were added to 40 mL of 80% ethanol aqueous solution and ultrasonically dispersed at a power of 300 W for 30 minutes. Subsequently, 0.22 g of KH570 (CAS number: 2530-85-0) and 1 mL of 25% ammonia solution were added. After continuous stirring at 300 rpm in a nitrogen environment at 55°C for 10 hours, the excess ethanol was removed by vacuum distillation, and the mixture was centrifuged at 10,000 rpm for 10 minutes. The precipitate was taken, washed four times with anhydrous ethanol, and vacuum dried at 60°C for 20 hours to obtain modified SiO2 / Fe3O4.
[0041] 95 g of acrylamide, 9 g of acrylic acid, 2.5 g of 2-acrylamido-2-methylpropanesulfonic acid sodium salt, 0.25 g of a double-tailed hydrophobic monomer, and 1.3 g of modified SiO2 / Fe3O4 were added to 570 mL of deionized water and mixed evenly. Sodium hydroxide was added to adjust the pH value to 6.2. Nitrogen was introduced into the solution and the mixture was stirred for 35 minutes. Then, 0.4 g of azobisisobutylamidine hydrochloride (CAS No.: 2997-92-4) was added. The mixture was stirred at 45°C and 450 rpm for 7 hours, then cooled to room temperature, washed four times with anhydrous ethanol, and the product was collected by filtration. It was vacuum dried at 45°C for 18 hours and pulverized into powder to obtain a dry powder drag reducer.
[0042] Example 4
[0043] After dissolving 1.2 g of 4-bromobutyryl chloride and 1.6 g of N-dodecylmethylamine in 35 mL of acetonitrile, the mixed solution was poured into a three-necked round-bottom flask equipped with a thermometer, reflux condenser, and dropping funnel. After mixing and stirring at a reaction temperature of 75°C and a speed of 500 rpm for 25 minutes, 3.9 g of polyethylene glycol monomethyl ether acrylate was added, and 35 mL of dichloromethane was added dropwise using a dropping funnel. After continuous stirring under a nitrogen atmosphere at 0°C for 46 hours, the crude product was washed four times with dichloromethane and 8.2% sodium bicarbonate solution, respectively, and then separated in a separatory funnel. The dichloromethane and acetonitrile were removed by rotary evaporation to obtain a double-tailed hydrophobic monomer (brown-yellow thick oily liquid).
[0044] 5.4 g of FeCl3·6H2O was placed in a 500 mL three-necked flask. Under nitrogen protection, 40 mL of 0.5 mol / L Na2SO3 solution was added and stirred for 10 min. Then, 6.7 mL of 25% ammonia water was quickly added and mixed. Black particles were formed. The temperature was raised to 70 ° C in a constant temperature water bath and 50 mL of 1% sodium citrate solution was added. The mixture was stirred at 500 rpm for 1.5 h, and then centrifuged at 8000 rpm for 13 min. The precipitate was washed with deionized water 4 times and finally dispersed in 50 mL of deionized water to obtain a stable Fe3O4 colloid. Under continuous stirring, 100 mL of 80% ethanol aqueous solution, 50 mL of Fe3O4 colloid and 0.42g of ethyl orthosilicate were added, and then 2.9mL of 25% ammonia water was added. The mixture was sealed and stirred at 300rpm for 6h, and then centrifuged at 10000rpm for 14min. The precipitate was taken and washed with deionized water and anhydrous ethanol four times respectively, and finally magnetic separation was performed to obtain core-shell SiO2 / Fe3O4 composite nanoparticles.
[0045] 5 g of core-shell SiO2 / Fe3O4 composite nanoparticles were added to 40 mL of 80% ethanol aqueous solution and ultrasonically dispersed at a power of 300 W for 30 minutes. Subsequently, 0.22 g of KH570 (CAS number: 2530-85-0) and 1 mL of 25% ammonia solution were added. After continuous stirring at 300 rpm in a nitrogen environment at 60°C for 10 hours, the excess ethanol was removed by vacuum distillation, and the mixture was centrifuged at 10,000 rpm for 10 minutes. The precipitate was taken, washed four times with anhydrous ethanol, and vacuum dried at 60°C for 20 hours to obtain modified SiO2 / Fe3O4.
[0046] 95 g of acrylamide, 9 g of acrylic acid, 3 g of 2-acrylamido-2-methylpropanesulfonic acid sodium salt, 0.2 g of a double-tailed hydrophobic monomer, and 1.4 g of modified SiO2 / Fe3O4 were added to 570 mL of deionized water and mixed evenly. Sodium hydroxide was added to adjust the pH value to 6.3. Nitrogen was introduced into the solution and mixed and stirred for 35 minutes. Then, 0.41 g of azobisisobutylamidine hydrochloride (CAS No.: 2997-92-4) was added. The mixture was stirred at 45°C and 450 rpm for 6 hours, then cooled to room temperature, washed three times with anhydrous ethanol, and the product was collected by filtration. It was vacuum dried at 40°C for 24 hours and ground into powder to obtain a dry powder drag reducer.
[0047] Example 5
[0048] After dissolving 1.2 g of 4-bromobutyryl chloride and 1.6 g of N-dodecylmethylamine in 35 mL of acetonitrile, the mixed solution was poured into a three-necked round-bottom flask equipped with a thermometer, reflux condenser, and dropping funnel. After mixing and stirring at a reaction temperature of 70°C and a speed of 500 rpm for 30 minutes, 3.9 g of polyethylene glycol monomethyl ether acrylate was added, and 35 mL of dichloromethane was added dropwise using a dropping funnel. After continuous stirring under a nitrogen atmosphere at 0°C for 47 hours, the crude product was washed twice with dichloromethane and 8.2% sodium bicarbonate solution, respectively, and then separated in a separatory funnel. The dichloromethane and acetonitrile were removed by rotary evaporation to obtain a two-tailed hydrophobic monomer (brown-yellow thick oily liquid).
[0049] 5.4 g of FeCl3·6H2O was placed in a 500 mL three-necked flask. Under nitrogen protection, 40 mL of 0.5 mol / L Na2SO3 solution was added and stirred for 10 min. Then, 6.7 mL of 25% ammonia water was quickly added and mixed. Black particles were formed. The temperature was raised to 70 ° C in a constant temperature water bath and 50 mL of 1% sodium citrate solution was added. The mixture was stirred at 500 rpm for 2 h. The mixture was centrifuged at 8000 rpm for 10 min. The precipitate was washed with deionized water for 3 times and finally dispersed in 50 mL of deionized water to obtain a stable Fe3O4 colloid. Under continuous stirring, 100 mL of 80% ethanol aqueous solution, 50 mL of Fe3O4 colloid and 0.42g of ethyl orthosilicate were added, and then 2.7mL of 25% ammonia water was added. The mixture was sealed and stirred at 300rpm for 7h, and then centrifuged at 10000rpm for 10min. The precipitate was taken and washed with deionized water and anhydrous ethanol for 5 times respectively, and finally magnetic separation was used to obtain core-shell SiO2 / Fe3O4 composite nanoparticles.
[0050] 5 g of core-shell SiO2 / Fe3O4 composite nanoparticles were added to 40 mL of 80% ethanol aqueous solution and ultrasonically dispersed at a power of 300 W for 30 minutes. Subsequently, 0.26 g of KH570 (CAS number: 2530-85-0) and 1 mL of 25% ammonia solution were added. After continuous stirring at 300 rpm in a nitrogen environment at 50°C for 12 hours, the excess ethanol was removed by vacuum distillation, and the mixture was centrifuged at 10,000 rpm for 10 minutes. The precipitate was taken, washed three times with anhydrous ethanol, and vacuum dried at 60°C for 22 hours to obtain modified SiO2 / Fe3O4.
[0051] 97 g of acrylamide, 9 g of acrylic acid, 3 g of 2-acrylamido-2-methylpropanesulfonic acid sodium salt, 0.26 g of a double-tailed hydrophobic monomer, and 1.5 g of modified SiO2 / Fe3O4 were added to 600 mL of deionized water and mixed evenly. Sodium hydroxide was added to adjust the pH value to 6.2. Nitrogen was introduced into the solution and stirred for 37 minutes. Then, 0.41 g of azobisisobutylamidine hydrochloride (CAS No.: 2997-92-4) was added. The mixture was stirred at 450 rpm at 45°C for 8 hours, then cooled to room temperature, washed three times with anhydrous ethanol, and the product was collected by filtration. It was vacuum dried at 50°C for 16 hours and pulverized into powder to prepare a dry powder drag reducer.
[0052] Example 6
[0053] After dissolving 1.2 g of 4-bromobutyryl chloride and 1.6 g of N-dodecylmethylamine in 35 mL of acetonitrile, the mixed solution was poured into a three-necked round-bottom flask equipped with a thermometer, reflux condenser, and dropping funnel. After mixing and stirring at a reaction temperature of 70°C and a speed of 500 rpm for 40 minutes, 3.9 g of polyethylene glycol monomethyl ether acrylate was added, and 35 mL of dichloromethane was added dropwise using a dropping funnel. After continuous stirring under a nitrogen atmosphere at 0°C for 48 hours, the crude product was washed twice with dichloromethane and 8.2% sodium bicarbonate solution, respectively, and then separated in a separatory funnel. The dichloromethane and acetonitrile were removed by rotary evaporation to obtain a double-tailed hydrophobic monomer (brown-yellow thick oily liquid).
[0054] 5.4 g of FeCl3·6H2O was placed in a 500 mL three-necked flask. Under nitrogen protection, 40 mL of 0.5 mol / L Na2SO3 solution was added and stirred for 10 min. Then, 6.7 mL of 25% ammonia water was quickly added and mixed. Black particles were formed. The temperature was raised to 70 ° C in a constant temperature water bath and 50 mL of 1% sodium citrate solution was added. The mixture was stirred at 500 rpm for 1 h. The mixture was centrifuged at 8000 rpm for 15 min. The precipitate was washed with deionized water for 5 times and finally dispersed in 50 mL of deionized water to obtain a stable Fe3O4 colloid. Under continuous stirring, 100 mL of 80% ethanol aqueous solution, 50 mL of Fe3O4 colloid and 0.42g of ethyl orthosilicate were added, and then 2.7mL of 25% ammonia water was added. The mixture was sealed and stirred at 300rpm for 5h, and then centrifuged at 10000rpm for 15min. The precipitate was taken and washed with deionized water and anhydrous ethanol three times respectively, and finally magnetic separation was used to obtain core-shell SiO2 / Fe3O4 composite nanoparticles.
[0055] 5 g of core-shell SiO2 / Fe3O4 composite nanoparticles were added to 40 mL of 80% ethanol aqueous solution and ultrasonically dispersed at a power of 300 W for 30 minutes. Subsequently, 0.2 g of KH570 (CAS number: 2530-85-0) and 1 mL of 25% ammonia solution were added. After continuous stirring at 300 rpm in a nitrogen environment at 65°C for 12 hours, the excess ethanol was removed by vacuum distillation, and the mixture was centrifuged at 10,000 rpm for 10 minutes. The precipitate was taken, washed three times with anhydrous ethanol, and vacuum dried at 60°C for 24 hours to obtain modified SiO2 / Fe3O4.
[0056] 90 g of acrylamide, 10 g of acrylic acid, 2 g of 2-acrylamido-2-methylpropanesulfonic acid sodium salt, 0.3 g of a double-tailed hydrophobic monomer, and 1.2 g of modified SiO2 / Fe3O4 were added to 600 mL of deionized water and mixed evenly. Sodium hydroxide was added to adjust the pH value to 6.0. Nitrogen was introduced into the solution and stirred for 40 minutes. Then, 0.43 g of azobisisobutylamidine hydrochloride (CAS No.: 2997-92-4) was added. The mixture was stirred at 450 rpm at 40°C for 5 hours, cooled to room temperature, washed with anhydrous ethanol 5 times, and the product was collected by filtration. It was vacuum dried at 50°C for 16 hours and pulverized into powder to prepare a dry powder drag reducer.
[0057] The present invention also carried out comparative examples and related tests.
[0058] Comparative Example 1 Compared with Example 2, the only difference is that no double-tailed hydrophobic monomer is added. Other preparation methods and components are exactly the same, and a dry powder drag reducer is finally prepared.
[0059] Comparative Example 2 Compared with Example 2, the only difference is that modified SiO2 / Fe3O4 is not added. The other preparation methods and components are exactly the same, and a dry powder drag reducer is finally prepared.
[0060] Comparative Example 3 Compared with Example 2, the only difference is that nano-silica is directly used instead of modified SiO2 / Fe3O4. The other preparation methods and components are exactly the same, and a dry powder drag reducer is finally prepared.
[0061] Performance testing The dry powder drag reducers prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to performance index tests. The specific test process is as follows: Preparation: Preparation of brine (100,000 ppm mineralization): The brine with a mineralization of 100,000 ppm is prepared from sodium chloride, calcium chloride and deionized water, wherein the sodium chloride content is 80,000 ppm and the calcium chloride content is 20,000 ppm.
[0062] (1) Drag reduction rate detection The dry powder drag reducers prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were dissolved in tap water to prepare a sample with a mass concentration of 0.5%. After stirring evenly, the clear water drag reduction rate of the sample was measured using a flow loop friction test device in accordance with SY / T6376-2008 "General Technical Requirements for Fracturing Fluids". The clear water drag reduction rate was calculated as follows: ;
[0063]
[0064] Where: is the stable pressure difference when clean water flows through the pipeline, Pa; is the stable pressure difference when the drag reducer flows through the pipeline, Pa. is the clear water drag reduction rate.
[0065] The drag reduction rates of the dry powder drag reducers prepared in Examples 1 to 6 and Comparative Examples 1 to 3 dissolved in salt water with a salinity of 100,000 were tested with reference to the above-mentioned clear water drag reduction rate, and the salt water drag reduction rate was finally calculated.
[0066] (2) Kinematic viscosity test 0.3 g of the dry powder drag reducer samples prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were weighed and dissolved in 300 g of the above-prepared brine, stirred at 3000 rpm for 3 min using a high-frequency stirrer, and the kinematic viscosity (mm) was measured using a Penn viscometer (inner diameter 0.8 mm). 2 / s).
[0067] The above specific test results are shown in Table 1.
[0068] As shown in Table 1, the dry powder drag reducers prepared in Examples 1 to 6 of the present invention maintain good drag reduction performance in both clean water and 100,000 salinity salt water, which is significantly improved compared to Comparative Examples 1 to 3. In the 100,000 salinity salt water, the drag reduction rate can still be maintained at more than 80%. After high-speed shearing in the 100,000 salinity salt water, the kinematic viscosity reaches 3.0 mm. 2 / s or more, and can maintain a high viscoelasticity, which further demonstrates its good shear resistance and remarkable salt resistance. The absence of key components in Examples 1 to 3 has a significant impact on the drag reduction rate and kinematic viscosity.
[0069] The dry powder drag reducers prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were placed in a 120°C environment for 90 days. The clear water drag reduction rate and salt water drag reduction rate were then tested again. The clear water drag reduction retention rate and salt water drag reduction retention rate of the samples after 90 days in a 120°C environment were calculated. The results are shown in Table 2.
[0070] As can be seen from Table 2, the dry powder drag reducers prepared in Examples 1 to 6 of the present invention have a higher drag reduction retention rate than that in Comparative Examples 1 to 3, that is, the drag reducer performance is better. After being placed at high temperature for a long time, the drag reduction retention rate of the dry powder drag reducers prepared in Examples 1 to 6 is significantly better than that in Comparative Examples 1 to 3, indicating that the dry powder drag reducer prepared by the technical solution of the present invention not only has excellent drag reduction performance, but also has high temperature resistance and good stability, and can be better applied to fracturing operations in the drilling process.
[0071] The above is a preferred embodiment of the present invention. Those skilled in the art may make several improvements and modifications without departing from the principles of the present invention. These improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a dry powder drag reducer for fracturing fluid, characterized in that: The steps include: S1. Dissolve 4-bromobutyryl chloride and N-dodecylmethylamine in acetonitrile, heat and stir to react, add polyethylene glycol monomethyl ether acrylate and dichloromethane, stir and react under nitrogen atmosphere, wash, separate, and rotary evaporate to obtain a double-tailed hydrophobic monomer; S2, adding the core-shell SiO2 / Fe3O4 composite nanoparticles to an ethanol aqueous solution, ultrasonically dispersing them, then adding KH570 and ammonia solution, stirring continuously for reaction, and then distilling under reduced pressure, centrifuging, collecting the precipitate, washing, and vacuum drying to obtain modified SiO2 / Fe3O4; S3. Add acrylamide, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid sodium salt, a double-tailed hydrophobic monomer, and modified SiO2 / Fe3O4 into deionized water and mix well. After adjusting the pH value, introduce nitrogen gas into the mixture and stir. Add an azo initiator, continue stirring to react, cool to room temperature, wash, filter, vacuum dry, and grind into powder to obtain a dry powder drag reducer.
2. The method for preparing a dry powder drag reducer for fracturing fluid according to claim 1, characterized in that: In step S1, 4-bromobutyryl chloride and N-dodecylmethylamine are dissolved in acetonitrile, and the mixture is stirred at a reaction temperature of 70-80° C. and a speed of 500 rpm for 20-40 minutes. Polyethylene glycol monomethyl ether acrylate is then added, and dichloromethane is added dropwise. The mixture is stirred continuously for 45-48 hours under a nitrogen atmosphere at 0° C., and then washed with dichloromethane and a sodium bicarbonate solution with a mass concentration of 8.2% for 2-5 times, respectively. The mixture is then separated in a separation funnel and rotary evaporated to obtain a double-tailed hydrophobic monomer.
3. The method for preparing a dry powder drag reducer for fracturing fluid according to claim 1, characterized in that: The core-shell SiO2 / Fe3O4 composite nanoparticles are prepared by mixing an ethanol aqueous solution, Fe3O4 colloid and ethyl orthosilicate under continuous stirring, adding ammonia water, stirring at a speed of 300 rpm for 5-7 hours, centrifuging at a speed of 10000 rpm for 10-15 minutes, collecting the precipitate, and washing it with deionized water and anhydrous ethanol for 3-5 times respectively.
4. The method for preparing a dry powder drag reducer for fracturing fluid according to claim 3, characterized in that: The volume concentration of the ethanol aqueous solution is 80%, and the volume concentration of the ammonia water is 25%.
5. The method for preparing a dry powder drag reducer for fracturing fluid according to claim 3, characterized in that: The stirring reaction is carried out under a sealed condition, and after washing with deionized water and anhydrous ethanol for 3 to 5 times respectively, magnetic separation is performed to finally obtain core-shell SiO2 / Fe3O4 composite nanoparticles.
6. The method for preparing a dry powder drag reducer for fracturing fluid according to claim 3, characterized in that: The Fe3O4 colloid is prepared by mixing FeCl3·6H2O and Na2SO3 solutions under nitrogen protection, stirring for 10 minutes, rapidly adding ammonia water and mixing evenly, heating to 70°C and adding sodium citrate solution, stirring continuously at 500 rpm for 1-2 hours, centrifuging at 8000 rpm for 10-15 minutes, collecting the precipitate, washing with deionized water for 3-5 times, and finally dispersing in deionized water.
7. The method for preparing a dry powder drag reducer for fracturing fluid according to claim 6, characterized in that: The molar concentration of the Na2SO3 solution is 0.5 mol / L, the mass concentration of the sodium citrate solution is 1%, and the volume concentration of the ammonia water is 25%.
8. The method for preparing a dry powder drag reducer for fracturing fluid according to claim 1, characterized in that: In step S3, acrylamide, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid sodium salt, a double-tailed hydrophobic monomer, and modified SiO2 / Fe3O4 are added to deionized water and mixed evenly. Sodium hydroxide is added to adjust the pH value to 6.0-6.
5. Nitrogen is introduced into the solution and the mixture is stirred for 30-40 minutes. An azo initiator is added, and the mixture is stirred at 40-50°C and 450 rpm for 5-8 hours. The mixture is then cooled to room temperature, washed with anhydrous ethanol for 3-5 times, and the product is collected by filtration. The mixture is vacuum dried at 40-50°C for 16-24 hours and crushed into powder to obtain a dry powder drag reducer.
9. The method for preparing a dry powder drag reducer for fracturing fluid according to claim 1, characterized in that: The azo initiator is azobisisobutylamidine hydrochloride.
10. A dry powder drag reducer for fracturing fluid, characterized in that: The preparation method according to any one of claims 1 to 9 is used to prepare the composite material, comprising the following raw materials in parts by weight: 90 to 100 parts of acrylamide, 8 to 10 parts of acrylic acid, 2 to 3.5 parts of 2-acrylamido-2-methylpropanesulfonic acid sodium salt, 0.2 to 0.3 parts of a double-tailed hydrophobic monomer, 1.2 to 1.5 g of modified SiO2 / Fe3O4, and 0.39 to 0.43 parts of an azo initiator.
Citation Information
Patent Citations
Instant drag reducer and preparation method thereof
CN112979870A
Recyclable oil pipeline transportation magnetic nano drag reducer as well as preparation method and application thereof
CN113896820A
Preparation method of drag-reduction thickening fracturing aid
CN117510716A
Shearing-resistant high-drag-reduction high-viscosity slickwater drag reducer and preparation method thereof
CN119241765A
Cyclic structure betaine and double-tailed hydrophobic association polymer fracturing thickening agent and preparation method thereof
CN119505080A
Cited By
Dry powder drag reducer for fracturing fluid and preparation method of dry powder drag reducer
CN121135953A
Dry powder friction reducer for salt-tolerant fracturing fluid and preparation method thereof
CN122541627A